Indonesian Religious Leaders and Palestine: The Influence of Islamic and Christian Clergy in Shaping National Sentiment (Palestine Issues on Indonesian Society, 2024)
This paper explores the influence of Indonesian religious leaders, both Muslim and Christian, in shaping national sentiment towards Palestine. Given Indonesia's pluralistic religious landscape, religious figures play a key role in articulating and disseminating solidarity for Palestine. The study analyzes the sermons, speeches, and public statements of influential clerics and religious organizations, investigating how they frame the Palestinian cause within religious discourse. For Muslim leaders, this often revolves around Islamic solidarity with the oppressed, while Christian clergy focus on themes of justice and human rights. The paper examines the intersections between religious teachings and political advocacy, as well as the broader impact of these religious narratives on public opinion. By exploring the role of religious leaders in building solidarity movements, this paper sheds light on how religious sentiments intersect with political activism in Indonesia’s support for Palestine.